Relationship Between Re-visit Compliance and Menstrual Cycle Among Three-Month Injectable Contraception Acceptors at Independent Practice of a Midwife, Jember City - Nurma Widyawati, Rita; Bachri, Syaiful; Jamhariyah (Universitas Bondowoso, 2024)
Introduction: Compliance is related to a change in behavior from behavior that does not obey the rules to behavior that obeys the rules such as revisiting three-month injections on schedule so that it can affect changes in the acceptor's menstrual cycle. Method: Cross-sectional research approach. The population and samples in this study were mothers who made a three-month injection re-visit at Independent Practice of a Midwife as many as 60 samples using the chi-square test. Result: The results showed that most of the respondents were compliant with the three-month injection revisit as much as 60.00%. Most of them were 58.33% with irregular menstrual cycles. The statistical test results with the chi-square test obtained a p-value of 0.000 <α (0.05), so H0 was rejected and H1 was accepted, which means that there is a relationship between re-visit compliance and menstrual cycles in three-month injectable family planning acceptors at independent practice of a midwife, Jember City. Conclusion: This study showed that compliance with re-visits of three-month injectable family planning acceptors was able to increase the regular menstrual cycle and non-compliance with re-visits of three-month injectable family planning acceptors was able to increase the irregular menstrual cycle. It is expected for three-month injectable family planning acceptors to control the re-visit schedule regularly.